2011
DOI: 10.1111/j.1552-6569.2011.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among MRI‐Defined Spinal Cord Involvement, Brain Involvement, and Disability in Multiple Sclerosis

Abstract: Objective To determine the inter-relationships between MRI-defined lesion and atrophy measures of spinal cord involvement and brain involvement and their relationships to disability in a small cohort of patients with multiple sclerosis (MS). Background Although it is known that cervical spinal cord atrophy correlates with disability in MS, it is unknown whether it is the most important determinant when compared to other regions of the CNS. Furthermore, it is not clear to what extent brain and cord lesions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
75
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 44 publications
15
75
0
Order By: Relevance
“…23,24 Considering region-specific pathologic differences, prior studies have found limited correlations between measures of SC and brain atrophy (SC-CSA and BPF), suggesting that pathogenic mechanisms in MS evolve independently to an extent in the brain and SC, particularly in progressive phases of disease, supporting the idea that MS disease mechanisms may differentially affect specific regions of the CNS. 14,25,26 Our observations of moderate correlations between SC and retinal measures, but absent correlations between measures of SC and brain atrophy support the notion that MS disease pathology is nonuniform in distinct CNS compartments, 27,28 and suggest there are clinically relevant pathologic processes occurring in the SC and retina that are distinct from those in the brain. Moreover, our observations of stronger SC and retinal correlations in progressive patients support the view that immunopathologic and tissue injury mechanisms of MS differ by disease subtype, and may be indicative of more uniform pathologic changes occurring in PPMS and SPMS, although these progressive MS subtypes may not be equivalent pathologically.…”
Section: Resultssupporting
confidence: 69%
“…23,24 Considering region-specific pathologic differences, prior studies have found limited correlations between measures of SC and brain atrophy (SC-CSA and BPF), suggesting that pathogenic mechanisms in MS evolve independently to an extent in the brain and SC, particularly in progressive phases of disease, supporting the idea that MS disease mechanisms may differentially affect specific regions of the CNS. 14,25,26 Our observations of moderate correlations between SC and retinal measures, but absent correlations between measures of SC and brain atrophy support the notion that MS disease pathology is nonuniform in distinct CNS compartments, 27,28 and suggest there are clinically relevant pathologic processes occurring in the SC and retina that are distinct from those in the brain. Moreover, our observations of stronger SC and retinal correlations in progressive patients support the view that immunopathologic and tissue injury mechanisms of MS differ by disease subtype, and may be indicative of more uniform pathologic changes occurring in PPMS and SPMS, although these progressive MS subtypes may not be equivalent pathologically.…”
Section: Resultssupporting
confidence: 69%
“…The spinal cord is a common site of pathology in MS, occurring early in the disease course 12,25 and playing a role in the development of disability 11,[14][15][16][17]19,[21][22][23]28 ; such involvement includes overt multifocal inflammatory demyelinating lesions and the potential for tissue destruction (axonal loss/atrophy). 29 This study evaluated the role of brain and spinal cord 3T MRI in defining NEDA at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…10 A growing body of evidence has determined that spinal cord MRI involvement shows a particularly close association with MSrelated disability. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] In addition, spinal cord involvement manifests early in the disease course; such lesions in presymptomatic at-risk individuals predict conversion to overt MS. 25 Adding more relevance to the need to consider spinal cord involvement in MS is the observation that such involvement may progress independently from the brain.…”
mentioning
confidence: 99%
“…Only moderate correlations have been found between cervical cord atrophy and conventional and advanced MRI measures of brain damage, 45,46,51 suggesting that degenerative and inflammatory processes typical of MS affect the cord and the brain with dynamics that are partially independent.…”
Section: Correlations With Brain T 2 Lesion Volume and Other Mri Measmentioning
confidence: 95%